Meningkatkan Penguasaan Konsep IPA Melalui Penggunaan Buku Penuntun Praktikum Berbasis Inkuiri Terbimbing - Dewi, Ratna (Jurnal Pendidikan Progresif, 2018)
Effectiveness of integratid practicum in natural science based on guided inquiri. The research objective was to determine the effectiveness student worksheet based discovery learning for improving concept mastery of science. The research method was quasi experimental with preetest-posttest design. Random sample selection from population VIII SMPN 1 Natar South Lampung in academic year of 2016-2017, so that obtained VIIIB dan VIIL class as sample. Quantitative data in the from of pretest, posttest, and n-gain. Qualitative data in the form of observation result of practicality of learning proces and the student activity in learning. The result showed that the use of integratid practicum in natural science based on guided inquiri.to improve concept mastery of science. That showed with high n-gain of experiment class 1 is 0,70 and the experiment class 2 is 0,70. The practicality of learning proces and the student activity in learning is also very high, that is in experiment class 1 and experiment class 2 the practicality of learning proces is 85.38% and 84.04%, while student activity is 86.44% and 85.84%. Key words: Practicum guided book, guided inquiry, mastering of science concept. DOI: http://dx.doi.org/10.23960/jpp.v8.i1.201804